URGENSI PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA NOMOR 10 TAHUN 2020 TENTANG SYARAT PEMBERIAN ASIMILASI DAN HAK INTEGRASI BAGI NARAPIDANA DAN ANAK DALAM RANGKA PENCEGAHAN DAN PENANGGULANGAN PENYEBARAN COVID-19 DILIHAT DARI TUJUAN PEMIDANAAN - Christian Sutanto; Rugun Romaida Hutabarat (Jurnal Hukum Adigama, 2021)
The assimilation policy in the midst of the Covid-19 pandemic is given as the right of prisoners after fulfilling the requirements in the applicable legal rules. In the midst of the Covid-19 pandemic, prisons are a risky place because many prisons are uninhabitable due to overcapacity. The problem faced is the urgency of Regulation of the Minister of Law and Human Rights Number 10 of 2020 concerning the Requirements for Providing Assimilation and Integration Rights for Prisoners and Children in the Context of Preventing and Combating the Spread of Covid-19 seen from the theory of the purpose of punishment. The research method used is normative legal research.  The results showed that the concept of assimilation viewed from the perspective of the integrative punishment theory was considered unsynchronized because the purpose of punishment was to maintain legal order in society and improve the personality of the perpetrator while still paying attention to human rights, compared to imprisonment which had more negative impacts. This policy is in accordance with the concept of assimilation, namely the fulfillment of the requirements and conditions as stipulated in the laws and regulations. Prisoners who return to criminal acts after being released through the assimilation and integration program in the midst of the Covid-19 pandemic, it is necessary to take action from the government with weighted punishment and remain under the supervision of Bapas, namely video conference and group line / whatsapp so this program remains goes well.